TINJAUAN YURIDIS TENTANG KEPASTIAN HUKUM TERHADAP PERIZINAN RUMAH SAKIT DI NEGARA INDONESIA - yulisar khiat (to-ra, 2021)
To realize health development in Indonesia, the government has made improvements to both health services and services to the community. This is inseparable from the existing regulations regarding the provisions regarding ordering, classification and licensing of hospitals regulated in the provisions of Law Number 44 of 2009 concerning Hospitals, Regulation of the Minister of Health of the Republic of Indonesia Number 147 of 2010 concerning Hospital Licensing, Regulations Minister of the Republic of Indonesia Number 340 of 2010 concerning Hospital Classification and Decree of the Minister of Health of the Republic of Indonesia Number 2264 of 2011 concerning Implementation of Hospital Licensing and Permenkes 3 of 2020 concerning Hospital Classification and Licensing. Keywords: legal certainty, hospital licensing